Program Pemberdayaan Desa Peradaban Zakat BAZNAS Kabupaten Sukabumi Melalui Pembinaan Mitra Domba Garut - Husnul Khatimah; Nuradi Nuradi (JES (Jurnal Ekonomi Syariah), 2023)
This study aims at determining the level of success in the program of Zakat Civilization Village empowerments through fostering Garut sheep partners in Jampangtengah, Sukabumi. This program is one of the BAZNAS Sukabumi superior programs in empowering the dhuafa or mustahiq in Panumbangan Village in Jampangtengah. It was selected as the Pilot Village for the goal realizations of Zakat Civilization Village in Sukabumi which is the city of santri. This research uses a survey conducted by depth interviews, observation, and documentation through descriptive analysis methods with a qualitative approach. The results showed that the dhuafa who become partners with Garut goat farming is still in the coaching process to build a motivation to empower themselves. Eventhough there are the limitations of their economic and educational levels, but this condition is quite encouraging because of their awareness to donate regularly and take a part in religious studies carried out by companions facilitated by the BAZNAS of Sukabumi. It can be seen by the program participants who generally come from this region and always be the first position in collecting and managing the zakat fitrah throughout Sukabumi. An Effective synergy between BAZNAS and the assisted residents in the management of the main cage and the dhuafa’s cage will bring the empowerment of people in Panumbangan Village, Jampangtengah, both materially and spiritually.